2021
DOI: 10.1002/agj2.20885
|View full text |Cite
|
Sign up to set email alerts
|

Do post‐harvest crop residues in no‐till systems provide for nitrogen needs of following crops?

Abstract: Increased adoption of no‐till systems in the Northern Plains has led to an increased volume of post‐harvest crop residue. A cool climate coupled with short growing seasons benefits from a conservation tillage approach by increasing water storage in semi‐arid areas where weather conditions are variable each year. The short frost‐free period presents challenges for residue decomposition and the subsequent nutrient uptake period is reduced in heavy accumulated crop fields. A combination of soil management practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 173 publications
2
13
0
Order By: Relevance
“…An observation of immobilization of NO 3 -N by nonleguminous post-harvest crop residues is consistently observed in our studies and is supported by other studies (Alghamdi & Cihacek, 2021). Kaur et al (2018) observed similar results in other North Dakota soils in short-term incubations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An observation of immobilization of NO 3 -N by nonleguminous post-harvest crop residues is consistently observed in our studies and is supported by other studies (Alghamdi & Cihacek, 2021). Kaur et al (2018) observed similar results in other North Dakota soils in short-term incubations.…”
Section: Discussionsupporting
confidence: 93%
“…However, in cooler climates with highly variable precipitation, the rate of residue decomposition is less predictable, resulting in less certain N mineralization. This brings to question if changes are necessary in N management for no-till production in the cooler climates of the northern Great Plains and other parts of the United States (Alghamdi & Cihacek, 2021). Research in the region has not yet validated N availability of specific crop residues, which is essential to determine if producer fertilizer application needs are being met.…”
Section: Core Ideasmentioning
confidence: 99%
“…The balance of the competition for N in the soil between plants and microbes (Inselsbacher et al, 2010; Kuzykov & Xu 2013; Shimel & Bennet, 2004) influences N 2 O emissions. Microbial N demands can be increased after N fertilization because of the interaction between crop residues and the soil (Alghamdi & Cihacek 2021; Wang et al, 2021) and low plant cover contributes to high N availability. But, because of the short life cycle of rhizosphere microorganisms and the insufficient C to maintain its fast initial growth rates, N is released into the soil, becoming available for growing plants (Jacoby et al, 2017; Richardson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The average0.25emNH4+$$ {\mathrm{NH}}_4^{+} $$:NO3$$ {\mathrm{NO}}_3^{-} $$ ratio under wetting to 70% WFPS was 1.6 for winter wheat while it was 1.0 for crimson clover (Table 2). Limited nitrification or greater NO3normalN$$ {\mathrm{NO}}_3^{-}\hbox{--} \mathrm{N} $$ immobilisation perhaps reduced soil NO3normalN$$ {\mathrm{NO}}_3^{-}\hbox{--} \mathrm{N} $$ availability during winter wheat residue decomposition (Alghamdi et al, 2022; Alghamdi & Cihacek, 2022). Therefore, NO3normalN$$ {\mathrm{NO}}_3^{-}\hbox{--} \mathrm{N} $$ limitation perhaps influenced a lower rate of N 2 O production from nitrification and denitrification under winter wheat with greater potential for complete denitrification to reduce N 2 O to N 2 in presence of available C (Table 2).…”
Section: Discussionmentioning
confidence: 99%